A prospective study of diagnostic conversion of major depressive disorder to bipolar disorder in pregnancy and postpartum. (16th October 2013) - Sharma, Verinder; Xie, Bin; Campbell, M Karen; Penava, Debbie; Hampson, Elizabeth; Mazmanian, Dwight; Pope, Carley J
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study was to determine the rate of, and risk factors for, a change in diagnosis from major depressive disorder to bipolar disorder, and from bipolar II disorder to bipolar I disorder in pregnancy and postpartum. Methods Patients with a prior history of major depressive disorder or bipolar II disorder were recruited between 24 and 28 weeks' gestation and followed through to one year postpartum. Diagnostic interviews were conducted using the Structured Clinical Interview for DSM‐IV at study intake and repeated using the Mini‐International Psychiatric Interview at one, three, six, and 12 months after childbirth. Fisher's exact test was used to assess the association between various risk factors and diagnostic switch. Results A total of 146 participants completed the intake interview and at least one follow‐up interview postpartum. Of these, 92 were diagnosed with major depressive disorder and 54 with bipolar II disorder at intake. Six women (6.52%) experienced a diagnostic change from major depressive disorder to bipolar II disorder during the first six months after childbirth. There were no cases of switching to bipolar I disorder, but in one participant the diagnosis changed from bipolar II disorder to bipolar I disorder during the three months after childbirth. Bipolar switch was associated with a family history of bipolar disorder. Conclusions The postpartum period appears to be a time of high risk for a new onset of hypomania in women with major depressive disorder. Our rate of diagnostic switching to bipolar II disorder (6.52%) is at least 11‐ to 18‐fold higher than the rates of switching in similar studies conducted in both men and women.